2012
DOI: 10.1155/2012/980910
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus Enhances Cyclosporine A-Induced Cytotoxicity in Human Renal Glomerular Mesangial Cells

Abstract: End Stage Renal Disease (ESRD) is an ever increasing problem worldwide. However the mechanisms underlying disease progression are not fully elucidated. This work addressed nephrotoxicity induced by the immunosuppressive agents' cyclosporine A (CsA) and sirolimus (SRL). Nephrotoxicity is the major limiting factor in long term use of CsA. SRL causes less nephrotoxicity than CsA. Therefore investigations into the differential effects of these agents may identify potential mechanisms of nephrotoxicity and means to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…One in vitro study showed that rapamycin and cyclosporine A synergistically upregulated human mesangial cells' (HMCs) CCN2 expression and may also exert profibrotic effects. 35 Another in vitro study showed that rapamycin promoted CCN2 mRNA and protein expression in rat mesangial cells (RMCs) in transcriptional way. 36 An in vivo study 37 used a rat model of chronic nephrotoxicity to show that rapamycin further augmented CCN2 expression in kidney tissue and promoted kidney fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…One in vitro study showed that rapamycin and cyclosporine A synergistically upregulated human mesangial cells' (HMCs) CCN2 expression and may also exert profibrotic effects. 35 Another in vitro study showed that rapamycin promoted CCN2 mRNA and protein expression in rat mesangial cells (RMCs) in transcriptional way. 36 An in vivo study 37 used a rat model of chronic nephrotoxicity to show that rapamycin further augmented CCN2 expression in kidney tissue and promoted kidney fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Findings that used other cell models are consistent with our results. One in vitro study 31 showed that rapamycin and cyclosporine A synergistically upregulated human mesangial cells' CTGF expression and may also exert profibrotic effects. Another in vitro study showed that rapamycin activated CTGF promoter and promoted CTGF mRNA and protein expression in rat mesangial cells (RMCs).…”
Section: Discussionmentioning
confidence: 99%
“…O’Connell and colleagues28 noted that cyclosporine used in concert with sirolimus had the effect of enhancing neural toxicity. Cyclosporine has also been shown to promote neoplasm and may cause neurotoxicity, hypertension, hyperlipidemia, and nephrotoxicity 29,30.…”
Section: Preclinical Studies and Adverse Effectsmentioning
confidence: 99%